Degeneration and Regeneration of Subbasal Corneal Nerves after Infectious Keratitis: A Longitudinal In Vivo Confocal Microscopy Study - Müller, Rodrigo (Ophthalmology, 2015)
PURPOSE: To investigate the longitudinal alterations of subbasal corneal nerves in patients with infectious keratitis (IK) during acute phase, cessation of treatment and recovery phase by in vivo confocal microscopy (IVCM). DESIGN: Prospective, longitudinal, case-control, single-center study. SUBJECTS: Fifty-six eyes of 56 patients with the diagnosis of bacterial (n=28), fungal (n=15), and Acanthamoeba (n=13) keratitis were included in the study. Thirty eyes of 30 normal volunteers constituted the control group. METHODS: Corneal sensation and serial IVCM of the central cornea were performed prospectively, by using the Heidelberg Retina Tomograph 3/Rostock Cornea Module (Heidelberg Engineering, Germany). IVCM images were assessed at 3 time points: at the first visit of the patient to the cornea service, at cessation of antimicrobial treatment, and up to six months after the resolution of infection. MAIN OUTCOME MEASURES: Total nerve number and length, main nerve trunks, branching and corneal sensation were assessed during the follow-up period. RESULTS: Corneal nerves were significantly reduced during the acute phase in eyes with IK compared with controls across all subgroups, with total nerve length of 5.47 ± 0.69 vs. 20.59 ± 1.06 mm/mm(2); p<0.0001. At the cessation of treatment, corneal nerves in patients with IK had regenerated, including total nerve length (8.49 ± 0.94; p=0.02) and nerve branch length (4.80 ± 0.37; p=0.005). During the recovery phase, after resolution of infection, corneal nerves further regenerated, including total nerve length (12.13 ± 1.97; p=0.005), main nerve trunk length (5.80 ± 1.00; p=0.01) and nerve branch length (6.33 ± 0.76; p=0.003) as compared to the acute phase, but were still significantly lower when compared to controls (p<0.05 for all parameters). Corneal degeneration and regeneration correlated with corneal sensation (r=0.47, p=0.0009). CONCLUSION: Patients with IK, suffering from profound loss of corneal nerves during the acute phase of infection, demonstrate an increase of corneal nerve density during the first six months after the resolution of infection. However, despite significant nerve regeneration, corneal nerve density does not fully recover and remains low as compared to controls. By providing an objective methodology to monitor corneal re-innervation, IVCM adds potentially important findings that may have implications for clinical management and surgical planning.